INNOVATION TECHNOLOGIES IN SOFT FRUIT PRODUCTION - D. Dunchev (Trakia Journal of Sciences)
The global challenges associated with climate change, food security and the growing instability with land and water shortages are changing the agriculture. The innovation technologies are crucially important to meet those issues and to improve productivity and sustainability of agricultural production. The aim of the study is to analyze the innovative technologies that could help farmers to improve soft fruit producing. The paper uses various methods of analysis – graphic, comparative and statistical. The new technologies in high-tech greenhouse horticulture are observed. The survey focuses on sensors (sensors for measuring water and air temperature, advanced sensors to determine microclimate and the activity of the crop) energy solutions, production technology, polytunnels, precision irrigation and robotics. The results indicate that the innovation technologies could improve water and nutrient use efficiency, increase yields and reduce the environmental impact. The innovation technologies in fruit sector are also important for human health. The implementation of innovative methods could stimulate the production of quality fruits which are environmentally friendly and internationally competitive.